IMPLEMENTASI TERAPI MUSIK TERHADAP PERILAKU HIPERAKTIF ANAK AUTIS DI RA IT THOYYIBAH KERASAAN KECAMATAN PEMATANG BANDAR KABUPATEN SIMALUNGUN - nurul saputri; rizka ramanda (Jurnal At-Tabayyun, 2023)
This research discusses the implementation of music therapyas an intervention approach for hyperactive behavior in early childhood. Focusing on the effects of music therapy on improving emotional balance and managing impulsivity, this study involved a number of early childhood participants who had been diagnosed with hyperactivity.The research methodology involved an experimental design with a control group and a treatment group receiving structured music therapy sessions over a specified period. Behavioral data is observed and recorded before, during and after the intervention, while also taking into account emotional responses through special evaluation tools.The research results show that music therapy can have a positive impact on increasing focus of attention, reducing levels of impulsivity, and increasing emotional balance in children who experience hyperactivity. These findings provide an important contribution to the understanding of the potential of music therapy as a non-pharmacological method in managing hyperactive behavior in early childhood, providing new insight into a holistic therapeutic approach in addressing neurobehavioral challenges in early developmental stages.